2017
DOI: 10.1159/000455962
|View full text |Cite
|
Sign up to set email alerts
|

Fiber Connections of the Caudal Corpus Cerebelli, with Special Reference to the Intrinsic Circuitry, in a Teleost (<b><i>Oreochromis niloticus</i></b>)

Abstract: The caudal part of the corpus cerebelli of Nile tilapia can be divided into dorsal and ventral regions. The granule cell layer of the dorsal (dGL) and ventral (vGL) regions of the caudal corpus cerebelli is known to receive indirect inputs from the telencephalon relayed by the nucleus paracommissuralis. The descending pathways are topographically organized, and the dGL and vGL receive inputs from different dorsal telencephalic parts. The caudal corpus cerebelli, in turn, projects extracerebellar efferents. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…Their axons ran medially and crossed the midline (Figure 5c’). These features are consistent with those of neurons in the inferior olivary nucleus of teleosts (Bae et al., 2009; Finger, 1978b; Imura et al., 2017; Takeuchi et al., 2015; Xue et al., 2008). By neural tracer injection into the cerebellum, some of parvalbumin‐ir neurons were retrogradely labeled contralaterally (Figure 5c”).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Their axons ran medially and crossed the midline (Figure 5c’). These features are consistent with those of neurons in the inferior olivary nucleus of teleosts (Bae et al., 2009; Finger, 1978b; Imura et al., 2017; Takeuchi et al., 2015; Xue et al., 2008). By neural tracer injection into the cerebellum, some of parvalbumin‐ir neurons were retrogradely labeled contralaterally (Figure 5c”).…”
Section: Resultssupporting
confidence: 84%
“…Most retrogradely labeled efferent cells lie in a restricted area the ventrolateral region of the auCe (Figure 6). Since tracer injections were limited to the midbrain which is but one of the efferent targets of teleost cerebellum, our experiment might not label all efferent cells, such as neurons, that project to caudal brain areas including the medulla (Ikenaga et al., 2002; Imura et al., 2017). However, neurons expressing vglut2 , which is considered as a marker for the cerebellar efferent neurons, distributed in regions identical to retrogradely labeled neurons, but not near the Purkinje cells in Polypterus cerebellum (Figure 9).…”
Section: Discussionmentioning
confidence: 99%
“…The present study revealed the presence of cerebello‐prethalamic projections in the yellowfin goby. Although connections of the cerebellum have been reported for various species of teleosts (e.g., catfish: Finger, 1978; false kelpfish: Murakami & Morita, 1987; goldfish and green sunfish: Wullimann & Northcutt, 1988; Nile tilapia: Imura et al, 2017; rainbow trout: Folgueira, Anadón, & Yáñez, 2006), a cerebello‐prethalamic projection has been found only in holocentrids (Xue et al, 2003). In the holocentrids, the cerebellar corpus is composed of dorsal and ventral lobes, and only the ventral lobe appears to project to the PTh, and only to the contralateral nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…The corpus cerebelli is separated into two subdivisions (dorsal and ventral) in holocentrid (Xue et al 2004). In the Nile tilapia, caudal region of corpus cerebelli can be subdivided into dorsa and ventral regions based on their cytoarchitechture and fiberconnections (Imura et al 2017). Mormyrid corpus was considered to be consist with four subdivisions traditionally (C1 to C4, Nieuwenhuys and Nicholson 1969a), but recent studies suggested that part of them belongs to the corpus and others to the valvula (see details in Meek and Nieuwenhuys 1998).…”
Section: Gross Morphology Of the Teleost Cerebellummentioning
confidence: 99%